Perspective: Reducing SARS-CoV2 Infectivity and Its Associated Immunopathology - Dubey, Abhishek; Dahiya, Surbhi; Rouse, Barry T.; Sehrawat, Sharvan (Frontiers in Immunology, 2020)
COVID-19 has become difficult to contain in our interconnected world. In this article, we discuss some approaches that could reduce the consequences of COVID-19. We elaborate upon the utility of camelid single-domain antibodies (sdAbs), also referred to as nanobodies, which are naturally poised to neutralize viruses without enhancing its infectivity. Smaller sized sdAbs can be easily selected using microbes or the subcellular organelle display methods and can neutralize SARS-CoV2 infectivity. We also discuss issues related to their production using scalable platforms. The favorable outcome of the infection is evident in patients when the inflammatory response is adequately curtailed. Therefore, we discuss approaches to mitigate hyperinflammatory reactions initiated by SARS-CoV2 but orchestrated by immune mediators.